Contemporary Management of Chylous Ascites after Retroperitoneal Surgery: Development of an Evidence-Based Treatment Algorithm. Issue 1 (25th July 2022) - Rose, Kyle M.; Huelster, Heather L.; Roberts, Erica C.; Manley, Brandon J.; Gilbert, Scott M.; Sexton, Wade J.
Abstract : Purpose: Chylous ascites (CA) is an uncommon complication that occurs from traumatic disruption of lymphatic channels after retroperitoneal surgery. The purpose of this study was to generate an evidence-based management strategy for CA by reviewing the current literature and available treatment modalities. Materials and Methods: A MEDLINE® literature review was performed for "chylous ascites." Individual patient data were extracted from case series and reports to create an efficacy analysis. Treatment modality, drain output, time to escalation of care and time to resolution were recorded. The efficacy analysis was utilized to generate a data-driven treatment algorithm. Results: The literature review yielded 1, 953 articles, from which 146 studies contributed data for 523 patients. The efficacy analysis included 245 patients, 168 (69%) of whom were managed successfully with conservative management (CM), at a median time to resolution of 11 days. Forty-eight patients underwent lymphangiography±embolization after CM, with a success rate of 85%. Thirty-one (12%) patients underwent surgical exploration. When treating CA, the patients who underwent stepwise management with CM followed by lymphangiography if CM failed experienced a resolution rate of 96.7%. An evidence-based treatment algorithm was created to guide treatment selection and duration of therapy before escalating to additional forms of therapy. Conclusions: In this report, we describe the largest conglomeration of iatrogenic CA cases from a literature review (523 cases) and efficacy analysis (245 cases), and created the first evidence-based treatment algorithm for this condition. Treatment success is substantial when using a stepwise combination of CM followed by lymphangiography±embolization.